2020
DOI: 10.1098/rspb.2020.1947
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic exposure interacts with habitat degradation to affect behaviour and survival of juvenile fish in the field

Abstract: Coral reefs are degrading globally due to increased environmental stressors including warming and elevated levels of pollutants. These stressors affect not only habitat-forming organisms, such as corals, but they may also directly affect the organisms that inhabit these ecosystems. Here, we explore how the dual threat of habitat degradation and microplastic exposure may affect the behaviour and survival of coral reef fish in the field. Fish were caught prior to settlement and pulse-fed polystyrene microplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…For example, adult P. amboinensis collected in the central GBR WHA contained an average of four microdebris items per individual fish, with a range from zero to 131 items (Jensen et al, 2019). In the laboratory, larvae of the same species also showed high variability in microplastic intake (McCormick et al, 2020). Together, our results and those of previous studies indicate likely but inconsistent ingestion of microplastics by fish, particularly at environmentally relevant levels of exposure.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…For example, adult P. amboinensis collected in the central GBR WHA contained an average of four microdebris items per individual fish, with a range from zero to 131 items (Jensen et al, 2019). In the laboratory, larvae of the same species also showed high variability in microplastic intake (McCormick et al, 2020). Together, our results and those of previous studies indicate likely but inconsistent ingestion of microplastics by fish, particularly at environmentally relevant levels of exposure.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, characteristics of the species being investigated (such as feeding habits, trophic levels, morphology, and life stage) may also influence ingestion and depuration rates (Bour et al, 2018;Xu X. et al, 2020). For example, P. amboinensis larvae were reported to take up to 14 h to depurate transparent PS microspheres (200-300 µm, 167 microsphere.L −1 ) ingested during a 1 h exposure experiment (McCormick et al, 2020). In turn, microplastic exposure (i.e., 50 PET fibers of 50-500 µm in length, and 50 PE irregular fragments >63 µm per food pellet, with no color specification) of planktivorous adult goldfish Carassius auratus resulted in similar microplastic retention as our fish species (up to 3 of 50 beads and fibers ingested after 6 days), but in slower depuration rate (Grigorakis et al, 2017).…”
Section: Discussionmentioning
confidence: 55%
“…Still, alteration of fish behavior due to contaminant exposure has been identified as a potential driver of ecosystem change (Brodin et al, 2014). Fish behaviors are not only changing in response to traditional metal pollutants but also in response to a variety of anthropogenic stressors such as microplastics (McCormick et al, 2020), other emerging contaminants (Brodin et al, 2013; Dzieweczynski et al, 2016; Lagesson, Saaristo, et al, 2018; Vignet et al, 2015), elevated temperature (Biro et al, 2010; Briffa et al, 2013; Závorka et al, 2020), acidification (Nilsson et al, 2012), acoustic emissions (McCormick et al, 2018; Mills et al, 2020; Nedelec et al, 2017; Sabet et al, 2015), release of hatchery reared individuals (Roberts et al, 2011) and selective harvesting of bold and more exploratory individuals (Biro & Post, 2008). While various forms of fish and behavioral trials have been used in these studies, they all have in common that they show that anthropogenic stressors can affect fish's boldness (Figure 1), a personality trait that affects predation risk and therefore fitness (Lind & Cresswell, 2005; Smith & Blumstein, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the importance of pH‐driven behavior changes has recently been questioned (Clark et al, 2020). Increased boldness occurs also in response to elevated temperature as a consequence of energetic regulation on metabolism (Briffa et al, 2013) and to microplastics due to nutritional stress (McCormick et al, 2020). Fisheries modify the behavior of fish populations directly by selectively harvesting bold and exploratory individuals (Andersen et al, 2018; Arlinghaus et al, 2017) but also indirectly by generating acoustic emissions (McCormick et al, 2018; Sabet et al, 2015) and by stocking freshwater with bolder fish reared in hatcheries (Härkönen et al, 2014) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…MP fibers were shown to up-regulate glycerophospholipid metabolism, exacerbating oxidative damage and inflammation, and to down-regulate fatty acyl metabolism, inducing nutritional deficiency. McCormick et al (2020) showed by controlled experiments that damselfish that had been fed MP as part of the standard diet developed more risky behaviour; they suggested that this was caused by the need for more food forays because their stomachs were partially filled with the undigested plastics. This can obviously be a harmful effect in any animal that ingests microfibres.…”
Section: Fate and Environmental Effects Of Microfibres From Textilesmentioning
confidence: 99%